Maximillian Fly - Sage, Angie (Katherine Tegen Books, 2019)
In a world where some humans look very different from our world--some with wings, some with carapaces, but all human on the inside--Maximillian Fly, a man six feet two with long antenae and beautiful indigo wings, as well as multiple pairs of arms, just wants to stay out of trouble. In his city of Hope, protected from the Contagion by a huge dome, Maximillian opens his doors to two Wingless children who just need a place to hide.